Effects of 12 weeks of functional training vs. Muay Thai on cardiac autonomic modulation and hemodynamic parameters in older adults: a randomized clinical trial - Saraiva, Bruna T. C. [UNESP]; Franchini, Emerson; Ribeiro, Alex S.; Gobbo, Luís A. [UNESP]; Correia, Marília A.; Vanderlei, Luiz C. M. [UNESP]; Ferrari, Gerson; Tebar, William R.; Christofaro, Diego G. D. [UNESP] (Springer Nature, 2024)
Background: The elevated blood pressure (BP) and lower cardiac autonomic modulation (CAM) are associated with higher morbidity mortality risk among older adults. Although exercise is an important intervention for cardiovascular promotion, it is unclear whether combat sports training could benefit cardiovascular outcomes as much as autonomic in this population. This study compared the effects of 12 weeks of Muay Thai (MT) training against functional training (FT) on CAM and hemodynamic parameters in older adults. Methods: The sample consisted of 50 older adults (41 women; 66.0 ± 5.3 years old), who were equaly randomized into FT (n = 25) and MT (n = 25) intervention groups. CAM was measured by 30-min rest heart rate variability. Systolic blood pressure (SBP), diastolic blood pressure (DBP) and resting heart rate (RHR) were measured using an automatic oscillometric device. Pulse pressure (PP) and the double product (DP) were also calculated. The interventions were carried out three times a week, with 60-min length per session, during 12 consecutive weeks. The intensity of the interventions was measured using the subjective perception of exertion scale and by accelerometer. Two-factor repeated measures analysis of covariance was used for groups comparison, considering intervention group and body mass as factors. The 95% confidence interval of the difference (95%CIdif) was also calculated and the effect size was measured using partial eta squared (η2p). Results: CAM indices did not show significant changes across moments and intervention groups. In hemodynamic parameters, only in DBP was there an effect of the moment (F1,39 = 8.206; P = 0.007; η2p = 0.174, large) and interaction effect between group*moment (F1,39 = 7.950; P = 0.008; η2p = 0.169, large). Specifically, the MT group at the post-training moment showed lower DBP (P = 0.010; 95%CIdif = -13.3; -1.89) in relation to the FT group. Furthermore, the MT group showed a decrease in DBP during training (P = 0.002; 95%CIdif = -10.3; -2.6). Also, an increase in training intensity was also found over the 12 weeks in FT, with no difference between the groups. Conclusion: After 12 weeks of MT practice there was a reduction in DBP compared to FT in older adults. Trial registration: NCT03919968 Registration date: 01/02/2019.
Keywords: Aging; Blood Pressure; Combat sports; Exercise